2006
DOI: 10.1088/0957-4484/17/19/028
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of metallic nanowires on a ferroelectric template via photochemical reaction

Abstract: Fabrication of silver nanowires on a domain-patterned lithium niobate template by inducing a photochemical reaction in an aqueous solution is reported. Silver deposition occurs preferentially along the domain boundaries which separate antiparallel domains. The nanowires can reach lengths of hundreds of micrometres, and their location can be controlled by generating domain patterns of a desired configuration while their width depends on deposition conditions, such as temperature, solution concentration and ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
128
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(139 citation statements)
references
References 25 publications
8
128
3
Order By: Relevance
“…The Ag deposition is more pronounced at the 180 domain walls, in agreement with the previous reports. 14,25,26 The average relative height of the Ag nanowires, determined from line profiles, is 4.96 6 0.95 nm. However, from the AFM images and line profile in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ag deposition is more pronounced at the 180 domain walls, in agreement with the previous reports. 14,25,26 The average relative height of the Ag nanowires, determined from line profiles, is 4.96 6 0.95 nm. However, from the AFM images and line profile in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of this defect dipole can lead to increased band bending. 14 The resulting asymmetry in internal electric fields and corresponding electromechanical strains can be detected with Raman spectroscopy even a year after poling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Ferroelectric lithography is an approach based on patterning the spontaneous polarization inside ferroelectric crystals so as to engineer static electric field distributions, suitable for driving bottom-up assembly and nanodeposition at the surface of ferroelectric templates. 16 Besides electric field poling, 17 the spontaneous polarization in materials such as LiNbO 3 , can be modified through the chemical process of proton exchange. 18 This method accounts for a change in crystal lattice of the ferroelectric substrate creating a modification to the polarization and charge at the surface.…”
mentioning
confidence: 99%
“…[23][24][25] The nanopatterned features created using Ag nanoparticles possessed a uniform distribution with a size variation between 2 and 10 nm in both diameter and height. 24 Photochemical reduction on LiNbO 3 has been shown under certain conditions to result in nanopatterns which form along domain walls, 17 which have further been shown to be conducting. 26 Dunn and Tiwari have demonstrated photochemical reduction on both þZ and ÀZ surfaces, and have demonstrated that the power of the irradiation is a critical parameter.…”
mentioning
confidence: 99%